DNA Demethylation Pathways: Recent Insights. (January 2013) - Li, Cong-jun
DNA methylation is a major epigenetic regulatory mechanism for gene expression and cell differentiation. Until recently, it was still unclear how unmethylated regions in mammalian genomes are protected from de novo methylation and whether or not active demethylating activity is involved. Even the role of molecules and the mechanisms underlying the processes of active demethylation itself is blurred. Emerging sequencing technologies have led to recent insights into the dynamic distribution of DNA methylation during development and the role of this epigenetic mark within a distinct genome context, such as the promoters, exons, or imprinted control regions. This review summarizes recent insights on the dynamic nature of DNA methylation and demethylation, as well as the mechanisms regulating active DNA demethylation in mammalian cells, which have been fundamental research interests in the field of epigenomics.